The Effects of Temperature and Impact Velocity on the Shock Wave Response of Pore-Embedded Metallic Glasses - Indrajit Patra; Ahmed M. Abdulhadi; Fatima Safaa Fahim; Bashar S. Bashar; Taif Alawsi; Mohammad Salmani (Advances in Materials Science and Engineering)
In this work, the shock wave response of a pore-embedded CuZr metallic glass (PEMG) under different impact velocities (0.5–1.5 km/s) and initial temperatures (300–600 K) was evaluated through the molecular dynamics (MD) simulation. The results indicated that the nucleation and growth of nanoscale shear events around the pore were the dominant mechanisms for plastic deformation under the shock wave. It was also found that the increase in the impact velocity led to the filling of pore, which was due to the structural softening and the local temperature increment in the vicinity of pore. Moreover, the spall event originated from the formation and coalescence of tension transformation zones, leading to the formation of nanovoids in the system. At higher velocities, the spallation was accompanied with the formation of more nanovoids with smaller sizes, inducing the brittle failure in the system. The MD outcomes also showed that the increase in initial temperature decreased the shock pressure and flow shear stress and led to the smoother spallation in the PEMG.